2020
DOI: 10.1080/0309877x.2020.1774049
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to academic help-seeking: the relationship with gender-typed attitudes

Abstract: In recent years, male students at UK schools and universities have been falling behind their female peers in academic achievement. Previous studies have shown that male students are less likely than female students to seek academic help, but have not investigated the relationship between gender-typical attitudes and reluctance to seek academic help. In the present study, 162 students at six UK universities completed the Help-Seeking Scales and the Traditional Gender Script Questionnaire. Data from this survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…To increase subjective norms, Thomas and Tagler (2019) advocated conducting information campaigns about academic help seeking with key stakeholders, such as lecturers, family and other students. Similarly, Brown et al (2020) suggested that the promotion of academic help seeking demonstrating its benefits through educators with the use of role models can increase students' attitude towards academic help seeking. University campuses should therefore carefully plan the promotion of academic support by addressing the above-mentioned factors, such as reducing stigma.…”
Section: Discussionmentioning
confidence: 99%
“…To increase subjective norms, Thomas and Tagler (2019) advocated conducting information campaigns about academic help seeking with key stakeholders, such as lecturers, family and other students. Similarly, Brown et al (2020) suggested that the promotion of academic help seeking demonstrating its benefits through educators with the use of role models can increase students' attitude towards academic help seeking. University campuses should therefore carefully plan the promotion of academic support by addressing the above-mentioned factors, such as reducing stigma.…”
Section: Discussionmentioning
confidence: 99%
“…Even among university students, helpseeking can be affected by (traditional) gender roles (cf. Brown et al, 2020;Shnabel et al, 2016), according to which the male identity is traditionally associated with autonomy and self-reliance (Amemiya & Wang, 2017). At the same time, studies in secondary education showed that "effortless achieving" is not only more in line with the male gender role, but also entails psychological benefits for boys (Heyder & Kessels, 2016).…”
Section: Gendered Patterns Of Help-seeking Among Peersmentioning
confidence: 99%
“…Evidentemente, la comprensión de estas barreras podría permitir estrategias de mejora para el acceso y la prestación oportuna de ayudas académicas. Finalmente, aun cuando existen estudios respecto a factores o barreras que inciden en la búsqueda de ayuda en general (ver por ejemplo Brown et al, 2020;Chowdhury & Halder, 2019), son pocos los que se focalizan en las barreras específicas respecto a los apoyos académicos ofertados por las instituciones (e.g. Seamark & Gabriel, 2018).…”
Section: Apoyos Académicos Institucionales (Aai) En Universitarios Chilenosunclassified